Movement variation in infants born following IVF/ICSI with and without ovarian hyperstimulation - Schendelaar, Pamela (Study of serum leptin in well differentiated thyroid carcinoma: Correlation with patient and tumor characteristics, 2013)
The effect of in vitro fertilisation (IVF) on neurodevelopment is not fully understood. Probably, IVF does not affect traditional measures of neurodevelopment in infancy. Recently, an instrument, the Infant Motor Profile (IMP), was developed that evaluates the quality of motor behaviour. It includes the evaluation of movement variation (i.e. movement repertoire size), a parameter reflecting the integrity of cortical connectivity.